A Density Functional Prediction of the Geometries, Stabilities, and Electronic Properties of Nanosize Cage‐Like (InN)2n (n = 6–27, 45, 54) Semiconductor Materials. Issue 5 (30th March 2018) - Zhao, Run‐Ning; Han, Ju‐Guang; Duan, Yuhua
Abstract: Geometries and electronic properties of sphere‐like (InN)2 n ( n = 6–27, 45, 54) nanoclusters are investigated by using density functional theory with the gradient corrected PBE functional and with relativistic effect being taken into account. Interestingly, with increasing the size of nanoclusters, the inner space, averaged radius, the HOMO–LUMO gaps, and the charge transfers of the optimized stable (InN)2 n nanocages are generally increased, and the absorption spectra of (InN)2 n nanocages vary from long wavelength to short wavelength (blue shift). Such phenomenon reflects indirectly the quantum confinement effect and the remarkable semiconductor‐like behaviors. Particularly, the ionic bonds of surface atoms in nanosize (InN)2 n ( n = 6–27, 45, 54) cages become gradually dominating chemical bonding with increasing cage‐size n, indicating that large‐size (InN)2 n nanocages have a trend to be ionic semiconductors. The calculated results are in good agreement with available theoretical and experimental data. Abstract : Due to the particular stability along with enhanced charge transfers of surface atoms and distinct ionic semiconductor characters at large‐size cages, the (InN)2 n nanostructures are important semiconductors with many applications. With increasing cluster‐size n, the calculated energy gaps of (InN) n cages are increased and the quantum confinement effect is exhibited indirectly.